Partial lesion of dopamine neurons of rat substantia nigra impairs conditioned place aversion but spares conditioned place preference. (4th May 2017) - Lima, Bernardo F.C.; Ramos, Daniele C.; Barbiero, Janaína K.; Pulido, Laura; Redgrave, Peter; Robinson, Donita L.; Gómez-A, Alexander; Da Cunha, Claudio
Graphical abstract: Highlights: Rats with partial lesion of nigrostriatal dopamine failed to learn to avoid a place in which they experienced a bitter taste. Rats with this lesion learned as well as control rats to prefer a place in which they experienced a sweet taste. In both control and lesioned rats unconditioned responses to sweet and bitter tastes were intact and comparable. Therefore, a sub-set of nigrostriatal dopamine neurons play a role in aversion-, but not reward-driven associative learning. Abstract: Midbrain dopamine neurons play critical roles in reward- and aversion-driven associative learning. However, it is not clear whether they do this by a common mechanism or by separate mechanisms that can be dissociated. In the present study we addressed this question by testing whether a partial lesion of the dopamine neurons of the rat SNc has comparable effects on conditioned place preference (CPP) learning and conditioned place aversion (CPA) learning. Partial lesions of dopamine neurons in the rat substantia nigra pars compacta (SNc) induced by bilateral intranigral infusion of 6-hydroxydopamine (6-OHDA, 3 μg/side) or 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP, 200 μg/side) impaired learning of conditioned place aversion (CPA) without affecting conditioned place preference (CPP) learning. Control experiments demonstrated that these lesions did not impair motor performance and did not alter the hedonic value of the sucrose and quinine. The number of dopamine neurons in the caudal part of the SNc positively correlated with the CPP scores of the 6-OHDA rats and negatively correlated with CPA scores of the SHAM rats. In addition, the CPA scores of the 6-OHDA rats positively correlated with the tissue content of striatal dopamine. Insomuch as reward-driven learning depends on an increase in dopamine release by nigral neurons, these findings show that this mechanism is functional even in rats with a partial lesion of the SNc. On the other hand, if aversion-driven learning depends on a reduction of extracellular dopamine in the striatum, the present study suggests that this mechanism is no longer functional after the partial SNc lesion.